2016
DOI: 10.1371/journal.pone.0151819
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning and Learning Skills of Adolescent Children Born at Fewer than 26 Weeks of Gestation

Abstract: AimsTo assess the cognitive and behavioral aspects of executive functioning (EF) and learning skills in extremely preterm (EPT) children compared with term control children aged 10 to 15 years.MethodsA total of 132 of 134 (98% of all eligible survivors) EPT children born at the 2 Swedish regional tertiary care centers from 1992 to 1998 (mean age = 12 years, mean birth weight = 718 g, and mean gestational age = 24.4 weeks) and 103 matched term controls were assessed. General intelligence was assessed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 60 publications
1
34
1
4
Order By: Relevance
“…A total of 45 studies met all the inclusion criteria. Executive function data were provided by 35 of these studies (3360 children born preterm/low birthweight and 2812 term‐born controls) either in the study paper or after a request for additional data sent to the authors . The characteristics and main study results are given in (Tables SI, SII, and SIII, online supporting information; working memory, inhibition, and cognitive flexibility respectively).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 45 studies met all the inclusion criteria. Executive function data were provided by 35 of these studies (3360 children born preterm/low birthweight and 2812 term‐born controls) either in the study paper or after a request for additional data sent to the authors . The characteristics and main study results are given in (Tables SI, SII, and SIII, online supporting information; working memory, inhibition, and cognitive flexibility respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Also, for inhibition, there were only a small number of studies investigating the ends of the gestational age range. To be able to draw robust conclusions on whether there is an effect of gestational age on executive function, more studies in children born extremely preterm (<26wks gestational age) and moderate-to-late preterm (32-37wks gestational Aarnoudse-Moens et al 63 Anderson et al 32 Brecht et al 86 Brummelte et al 86 Campbell et al 88 Crotty et al 90 de Kieviet et al 21 Farooqi et al 61 Ford et al 91 Grunewaldt et al 93 Guarini et al 94 Hodel et al 62 Lohaugen et al 97 Mulder et al 18 Ni et al 98 Potharst et al 99 Ritter et al 100 Sayeur et al 101 Wehrle et al 102 Litt et al 96 Rose et al 24 -2.00 -1.00 0.00 1.00 2.00…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…66,7275 Two meta-analyses found that the performance of children born preterm on measures of executive control is, on average, 0.3 to 0.6 standard deviations lower than that of full term children, 63,64 although effects as great as 1 standard deviation have been reported in studies of children with extreme prematurity. 76 Rates of deficits in EF relative to age standards on tests and parent and teacher ratings are substantially higher for children with more extreme prematurity compared to NBW controls, with rates 2 to 4 times higher in one sample 65 and 3 to 5 times higher in another. 67 Impairments in EF are found even when excluding children with low IQs or when adjusting group comparisons for IQ or estimates of ‘crystallized’ intelligence based on vocabulary knowledge.…”
Section: Effects Of Preterm Birth On Executive Functionmentioning
confidence: 96%
“…Given that preterm birth and low birthweight are the leading causes of infant mortality and are associated with long-term cognitive developmental child and adult health issues, it is imperative to understand factors associated with these disparities (Farooqi, Adamsson, Serenius, & Hägglöf, 2016;Taylor & Clark, 2016).…”
Section: Introductionmentioning
confidence: 99%